(untitled) (Iraqi Journal of Civil Engineering, 2008)
Abstract:Many of researchers study the uses of chopped worn-out tires as a replacementmaterial to production special types of concrete. In presented work, the worn-out tireswere used as fibers which have dimensions of 1×1×3 cm. The fibers used as a partialreplacement from volume of coarse aggregate. Two mixes of fiber worn-out tires(F.W.T.) concrete in addition to reference mix were selected, using PartialReplacement Ratio (PRR) of 20% and 30%. The tests which were used in this studywere: compressive strength, splitting tensile strength and flexural strength. It wasfound that incorporating of F.W.T. in concrete effected negatively on most propertiesof concrete, for example the percentage decreases in compressive strength relative toreference mix at 28 day were 20% and 27.3% for concrete with 20% and 30% F.W.T.by volume of coarse aggregate respectively. However, it gave good indicator to beutilized as a new construction material in many applications.